Vitamin D Deficiency Is Associated With Metabolic Risk Factors in Women With Polycystic Ovary Syndrome: A Cross-Sectional Study in Shaanxi China - Wang, Li; Lv, Shulan; Li, Fen; Yu, Xuewen; Bai, E.; Yang, Xiaofeng (Frontiers in Endocrinology, 2020)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Obesity, hyperandrogenemia and insulin resistance (IR) are prevalent characteristics of PCOS. The aim of the study was to investigate the vitamin D status, and analyze the relationship between vitamin D deficiency and metabolic risk factors in women with PCOS in Shaanxi China. Methods: A cross-sectional study included 169 women diagnosed with PCOS and 114 control women without PCOS. The serum 25(OH)D and metabolic markers were measured. Vitamin D deficiency was defined as serum 25(OH)D concentration less than 20 ng/mL. The primary outcome was the difference in vitamin D status between the PCOS and control groups, the secondary outcomes were correlations between serum 25(OH)D concentration and metabolic risk factors in women with PCOS. Results: The serum 25(OH)D concentration was significantly lower in women with PCOS than in controls (P<0.05), and the prevalence rates of 25(OH)D deficiency and insufficiency were significantly higher in women with PCOS than in controls(P<0.05). The serum 25(OH)D concentration was significantly lower in PCOS women with obesity or IR than in women without obesity or IR (P<0.05), and the prevalence of 25(OH)D deficiency in PCOS women with obesity or IR was significantly higher than in women without obesity or IR(P<0.05). Serum 25(OH)D concentration was significantly negatively correlated with body mass index (BMI), waist-to-hip ratio (WHR), fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), total cholesterol, low-density lipoprotein cholesterol (LDL-C) and high-sensitivity C-reactive protein(hs-CRP) (P<0.05). In comparison, serum 25(OH)D concentration was significantly positively correlated with high-density lipoprotein cholesterol(HDL-C) (P<0.05). Increased BMI and WHR, high levels of fasting insulin, HOMA-IR, total cholesterol, LDL-C and hs-CRP were regarded as risk factors, but high level of HDL-C was considered to be protective factor of vitamin D deficiency in PCOS women. Conclusions: Vitamin D deficiency is prevalent in PCOS women in Shaanxi China, especially in those with obesity and IR. The serum 25(OH)D concentration was correlated with metabolic risk factors in PCOS women. Multi-centre randomized controlled trials with large sample sizes are needed to explore the metabolic role of vitamin D supplementation in women with PCOS.